90+9x=80+12x

Simple and best practice solution for 90+9x=80+12x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 90+9x=80+12x equation:


Simplifying
90 + 9x = 80 + 12x

Solving
90 + 9x = 80 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
90 + 9x + -12x = 80 + 12x + -12x

Combine like terms: 9x + -12x = -3x
90 + -3x = 80 + 12x + -12x

Combine like terms: 12x + -12x = 0
90 + -3x = 80 + 0
90 + -3x = 80

Add '-90' to each side of the equation.
90 + -90 + -3x = 80 + -90

Combine like terms: 90 + -90 = 0
0 + -3x = 80 + -90
-3x = 80 + -90

Combine like terms: 80 + -90 = -10
-3x = -10

Divide each side by '-3'.
x = 3.333333333

Simplifying
x = 3.333333333

See similar equations:

| 2x+c+12=78 | | 4x-14+3x=28 | | -12x^2-144x-432=0 | | 7x-4x+12= | | 9x-1=116 | | 9x-57.6=x | | -14x+3(2x-5)=-19-7x | | 4x-20=6x-40 | | 0.3x+0.5=-1.3 | | 3(n-5)=.4-.2(n-7) | | 2y+4=2x | | -12x^2-144x-216=0 | | 32-7x=14+11x | | 44+3x=(X+20) | | 78=5y | | 6x-7=3x+4 | | 6(x-6.5)=9.6 | | 0.2x=0.3 | | 19-4(x+4)=11(x+2)-1 | | 2+(-5)(h+3)=-28 | | -4y+4x=12 | | -3d=13 | | 2+(-5)(h+3)=28 | | y=10000+1x | | 4z-5z+6= | | 9(8x-9)=-351 | | -3y+2y+5=12 | | -4+3c+6=2c+2+c | | 2(x-5)+7=6x-4(1+x) | | 8(c-2)+4=3+c-15 | | 4x+6.46=2x+10 | | x^2-30x-63=0 |

Equations solver categories